Meta-Analysis of 3D Printing Applications in Traumatic Fractures - Yang, Sha; Lin, Huapeng; Luo, Cong (Frontiers in Surgery, 2021)
Background Trauma fracture is a common orthopaedic disease, and the application of 3D printing technology in fracture treatment is increasingly popular, but the effectiveness of 3D printing-assisted surgery still lacks high-level evidence to support its application. . Methods The Embase, PubMed and Cochrane Library databases were systematically searched until October 2020 to identify relevant studies. All randomized controlled trials (RCTs) comparing the efficacy of 3D printing-assisted surgery versus conventional surgery for traumatic fractures were obtained. RevMan V.5.3 software was used to conduct the meta-analysis. Results A total of 12 RCTs involving 641 patients were included. The pooled results showed that, compared with conventional surgery, 3D printing-assisted surgery was associated with a shorter operation duration (standardized mean difference (SMD)=-1.52, 95% confidence interval (CI) -1.70~-1.34, P＜0.00001), less intraoperative blood loss (SMD=1.34, 95% CI 1.74~0.94, P＜0.00001), fewer intraoperative fluoroscopies (SMD=1.25, 95% CI 1.64~0.87, P＜0.00001), a shorter fracture union time (SMD=-0.15, 95% CI -0.25~-0.05, P=0.003), and a higher rate of excellent outcomes (OR=2.40, 95% CI 1.07~5.37, P=0.03). There was no significant difference in complication rates between the two groups (OR=0.69, 95% CI 0.69~1.42, P=0.32). Conclusions According to indicators such as operation duration, intraoperative blood loss, number of intraoperative fluoroscopies, fracture union time, and the rate of excellent outcomes, the effect of 3D printing-assisted surgery in the treatment of trauma fractures was better than that of conventional surgery. There was no significant difference in the incidence of complications between the two approaches.